Fuel Properties of Slab Wastes from Sengon Sawmills: A Case Study in Sleman and Wonosobo Regencies - Joko Sulistyo; Binsar Edward Sianturi; Raditya Ananta Rustantoputro (Wood Research Journal, 2021)
Sengon (Paraserianthes falcataria (L.) Nielsen) is a fast-growing and versatile species that has been established in community forests. Many sawmills utilize sengon wood as a raw material which generates wastes in the form of sawdust and slab consisting of a mixture of bark and wood. Those wastes are widely used by communities and home industries as fuel. The objective of this study was to characterize the energy properties of slab wastes from sengon sawmills in Wonosobo dan Sleman Regencies. The results showed that the calorific value and fuelwood value index (FVI) ranges were 4,089 to 4,749 cal/g and 2.71 to 18.74, respectively. The values of density ranged from 0.23 to 0.94 g/cm3. The proximate analysis showed that the values of moisture and ash contents ranged from 13.90 to 20.03% and from 0.30 to 4.59%, respectively, whereas volatile matter and fixed carbon contents ranged from 75.84 to 88.94% and from 10.23 to 20.62%, respectively. In general, the slab samples from Wonosobo gave higher values in fixed carbon content and FVI but smaller values in density, moisture content, volatile matter content, and ash content than those of the samples in Sleman. The bark part showed higher amounts in density, moisture content, fixed carbon content, and ash content but lower in volatile matter content, calorific value, and FVI than the wood part. Based on the wood consumption, sawmill recovery, calorific value, and dry weight biomass value, the potential annual energy from slab wastes in Sleman and Wonosobo reached 1,374 × 1013 cal (equivalent to 1,525,222  L of kerosene) and 1.521 × 1014 cal (equivalent to 16,884,016 L of kerosene), respectively.